Enhanced Luminescent Probe Utilizing Schiff Base Ligand for 2,4,6-Trinitrophenol Detection in Aqueous Media - Altun, Ayhan; Buldurun, Kenan; Turan, Nevin (My University, 2025)
This research explored the fluorescence properties of a Schiff base ligand which was synthesized and characterized used by standard spectroscopic methods. The examination into its photophysical and fluorescent sensor properties involved UV-Vis spectroscopy, as well as fluorescence spectroscopy, time-resolved and steady-state. Fluorescent sensors were found to exhibit excellent sensitivity and selectivity for 1,3,5-trinitrophenol (TNP), over testing with other nitroaromatic (dinitrobenzene (DNB), 2,4,6-trinitrotoluene (TNT), 2,4-dinitrotoluene (DNT), 2-nitrophenol (2-NP), 4-nitrophenol (4-NP), and 2,4-dinitrophenol (DNP)), explosives with significant fluorescence “off” responses, resulting in immediate fluorescence color change. The binding mechanisms between Schiff base and TNP were assessed using Job’s drawing. The compound exhibited exceptional sensitivity in detecting TNP with an impressively low LOD of 0.253 μM covering a linear working range of 2.50-30.00 μM. The study revealed that the compound exhibited robust fluorescent properties, proved to be effective in fluorescence quenching-based TNP detection in water solutions, and demonstrated both high selectivity and sensitivity. This finding underlines the potential utility of this ligand as a promising tool in environmental monitoring or related fields where the detection of TNP is crucial.
Keywords: Schiff base, Fluorescent sensor, Nitroaromatic compounds, TNP